Weight Watchers on prescription: An observational study of weight change among adults referred to Weight Watchers by the NHS - Aston Louise M; Olson Ashley D; Ahern Amy L; Jebb Susan A (BMC, 2011)
Abstract Background The scale of overweight and obesity in the UK places a considerable burden on the NHS. In some areas the NHS has formed partnerships with commercial companies to offer weight management services, but there has been little evaluation of these schemes. This study is an independent audit of the Weight Watchers NHS Referral scheme and evaluates the weight change of obese and overweight adults referred to Weight Watchers (WW) by the NHS. Method Data was obtained from the WW NHS Referral Scheme database for 29,326 referral courses started after 2nd April 2007 and ending before 6th October 2009 [90% female; median age 49 years (IQR 38 - 61 years); median BMI 35.1 kg/m2 (IQR 31.8 - 39.5 kg/m2). Participants received vouchers (funded by the PCT following referral by a healthcare professional) to attend 12 WW meetings. Body weight was measured at WW meetings and relayed to the central database. Results Median weight change for all referrals was -2.8 kg [IQR -5.9 - -0.7 kg] representing -3.1% initial weight. 33% of all courses resulted in loss of ≥5% initial weight. 54% of courses were completed. Median weight change for those completing a first course was -5.4 kg [IQR -7.8 - -3.1 kg] or -5.6% of initial weight. 57% lost ≥5% initial weight. Conclusions A third of all patients who were referred to WW through the WW NHS Referral Scheme and started a 12 session course achieved ≥5% weight loss, which is usually associated with clinical benefits. This is the largest audit of NHS referral to a commercial weight loss programme in the UK and results are comparable with other options for weight loss available through primary care.